Analysis of Cost Variance in the Application of Target Costing as a Cost Control Tool at Haki Clothing Store Manado - Asty Tyara Karisoh; Herman Karamoy; Victorina Zusana Tirayoh (Indonesian Journal of Entrepreneurship and Startups, 2025)
Cost variance is the difference between budgeted costs and actual costs, which is often an indicator of efficiency in corporate financial management. This study aims to analyze the cost variance that occurs at Haki Clothing Store related to the target costing strategy as a cost control tool. This research uses a qualitative descriptive method, which is focused on evaluating cost variances in production and operations. The results showed that cost variances appeared in several aspects such as clothing production, labor, electricity, and employee meals. Haki Clothing store experienced cost inefficiencies in several categories such as production costs due to printing errors, electricity costs that were higher than the target, and food costs that increased due to price increases. However, cost efficiency was also found in the category of lower employee bonuses due to leave taken. These results emphasize the importance of more careful budget planning and tight control of operating costs to improve efficiency and maintain store profitability.